Self-perception of voice in Spanish-speaking Trans Women in Santiago: first Chilean study - Orellana Venegas, Carolina; Marín Garrido, Fabiola; Muñoz, Luciana Daniela (Revista Chilena de Fonoaudiología, 2021)
At the international level, it is recognized that transgender women, due to their voice, experience psychosocial consequences on a daily basis. In Chile there is no background on this issue, so it is necessary to collect information that allows verifying the background obtained in the international literature. Therefore, the objective of the work is to describe the self-perception of the voice of a group of transgender women from the Metropolitan Region, according to the Trans Woman Voice Questionnaire (TWVQ) instrument. For this, an observational, descriptive correlational cross-sectional study with a quantitative approach was carried out, which was approved by the Ethics Committee of the Faculty of Medicine - Clínica Alemana Universidad del Desarrollo (GP-70/2018). Thirty transgender women participated, responding first to a medical history questionnaire and then to the TWVQ. The latter was analyzed based on the total score and its three items (anxiety and avoidance, vocal function and vocal identity). The results show that voice self-perception is affected first by the vocal function item, then by the anxiety and avoidance item, and finally by the vocal identity item, according to perceived difficulty. The data also provide preliminary evidence that self-perception of the voice could be associated with attendance at the voice specialist and with the length of time on hormonal therapy. Finally, the study provides an empirical way to analyze the TVWQ in detail, based on the proposal of three items.